A praça-identidade e apropriação pública : avaliação pós-ocupação da Praça Arthur Thomas no município de Umuarama - Paraná - Silva, Regina de Held (2009)
The squares are spaces of social cohesion, of urban existences, of intense symbolyze and perhaps, it is still the only morphologic element capable to express the sense maximum of urbe, in respect and valorization of the urban life. However, for that happens, it is done necessary to rediscover them front to the abrupt world contemporary changes of social order, cultural, economical and politics. That research consists of a Post-Occupancy Evaluation (POE), which seeks to interpret these changes in the manifestations of the physical environmental phenomena and the forms of human involvement with the Arthur Thomas - Square, a referential centrality park in the municipal district of Umuarama, Paraná. As in every study of ERBs (Environmental Relations and Behavior), it was assumed the multiple and interdisciplinary posture for they be applied the multimethods concepts in the evaluation of the perceptive actings elements that compose the Arthur Thomas' Square. As the square unique phenomena, your analyses need to be revaluated of the methodological tool point, adapting them for the diagnosis of the variables phenomenological existent. In those terms, the GAM (Grid of Attributes Method) it was adapted, and the analysis of the data leads to the perception of the priority attributes, capable to synthesize it in two phenomena: an existentialist phenomenon and the other space, as support to the existentialist. They are the shelter and the communication. The two phenomena transcend the current drawing of the, squares and they prove the importance of the shelter sensation, resultant of the shadow of the trees, as space support for the existential phenomenon, in other words, of the intense verbal and visual interrelationship that happens at the square. So, that research, through the special syntax or eidetic reducing of the square, attests the importance of the urban green for the manifestation of intrinsic values to the human existence. The formulated methodological interconnection, among: the morphologic studies, GAM and the reducing analysis, seek to break with the analytic paradigms for the study of squares, when evaluating their attributes starting from the users' cognitive aspects, considering her inserted in their urban context. That diagnosis form generates project subsidies that allow enlarging their symbolic potentials, through interventions that it really qualifies the Arthur Thomas' Square. It is expected that the proposed analytic procedures can be reproduced at other referential centrality squares, of the same municipal district, or others (of medium and small size) of the North and Northwest area of the State of Paraná, always with the correct methodological adaptations to the phenomenological variables and, like this, they can contribute in add to other take part practices of urban planning and maintainable administrations of the urban atmosphere.